INFRASTRUKTUR LIMBAH TERPADU DALAM TAMAN LINGKUNGAN PERMUKIMAN - Djajeng Poedjowibowo (Jurnal Lanskap Indonesia, 2011)
Residential areas are inevitably identified as waste generating region. In general, the waste from the residential area will be transfered from the collecting tool into the garbage carrier at transfer depot which has about 200 m2 area. A residential area of about 10,000 inhabitants requires at least an area of    5,000 m2, generating approximately 25 m3 of waste per day. When transporting all the waste to a landfill, a raise in operating cost and pollution is expected along with odors and garbage scattered along the path. To solve this problem, transfer depot shall be empowered as Integrated Waste Treatment Facility (TPSAT). Transfer depot and neighborhood park is a crucial requirement of a residential area. Integration of both facilities could reduce the negative image of Transfer Depot. TPSAT will produce material that can be recycled, and also organic fertilizer that can be used for maintaining plants growth. While in process of sorting, cleaning, and composting definitely require lots of water. The spacious garden environment can simultaneously be used as a collecting andprocessing area of grey water from surrounding settlements. Waste Water Treatment with Garden (WWG) will produce water that can be used in the process of washing and flushing recycling materials and watering organic fertilizer. Eco-technology tub with 500 m2 area in the depth of 0.8 m ables to generate clean water from greywater at the rate of  100 m3/day generates from 1,000 inhabitant. Park, which is also considered as the lung of environment and communal space, can be integrated and used as local TPSAT WWTP when used with proper layout design and suitable plants.